Mendeteksi Orisinalitas Citra Menggunakan Teknik Error Level Analysis dan Metadata - Rian Abrori; Maulidah Fitria; Habi Bullah (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The current development of digital image technology is often misused by certain parties to carry out fraudulent acts that can harm other people, for example what is often encountered in society is proof of bank transfers that have been manipulated. This study aims to detect image originality in an image using the Error Level Analysis (ELA) and Metadata techniques in Forensicallybeta web-based applications. Research model by completing two image files consisting of original images and manipulated images. The results showed that Forensicallybeta with the Error Level Analysis (ELA) and Metadata techniques were able to detect the authenticity of an image, so it was appropriate to determine whether the image file was original or manipulated